Securing PHP Apps - Edmunds, Ben (Apress, 2016)
Secure your PHP-based web applications with this compact handbook. You'll get clear, practical and actionable details on how to secure various parts of your PHP web application. You'll also find scenarios to handle and improve existing legacy issues.Is your PHP app truly secure? Let's make sure you get home on time and sleep well at night. Learn the security basics that a senior developer usually acquires over years of experience, all condensed down into one quick and easy handbook. Do you ever wonder how vulnerable you are to being hacked? Do you feel confident about storing your users' sensitive information? Imagine feeling confident in the integrity of your software when you store your users' sensitive data. No more fighting fires with lost data, no more late nights, your application is secure.